Application of Pulsed Electric Field as a Pre-Treatment for Subcritical Water Extraction of Quercetin from Onion Skin - Han-Sol Kim; Min-Jung Ko; Chan-Ho Park; Myong-Soo Chung (Foods, 2022)
Pulsed electric field (PEF) treatment promotes the electroporation of biological membranes, and if included as a pre-treatment, could improve the extraction of certain constituents therefrom. The aim of this study was to determine the optimal extraction conditions for extracting the flavonoid quercetin from dried onion skin and to establish whether the yield could be enhanced by combining PEF pre-treatment with an eco-friendly extraction method that uses subcritical water extraction (SWE). Samples of onion skin were treated with PEF under conditions of varying electric field strength (0.5–2.5 kV/cm) and duration (5–120 s). SWE was then performed with an extraction time of 15 min and at temperatures ranging from 105 °C to 185 °C. Among the conditions tested, the yield of total quercetin was the highest after pretreatment with PEF at 2.5 kV/cm for 15 s, followed by SWE at 145 °C for 15 min (yield 19.25 ± 0.77 mg/g dried onion skin, mean ± standard deviation). Pretreatment with PEF improved the yield of total quercetin extracted by 33.22% compared with the PEF-untreated samples. These findings demonstrate that pretreatment of onion skin with PEF has the potential to improve flavonoid extraction.